2015
DOI: 10.1042/bj20140428
|View full text |Cite
|
Sign up to set email alerts
|

Decreased adipogenesis and adipose tissue in mice with inactivated protein phosphatase 5

Abstract: Glucocorticoids play an important role in the treatment of inflammation and immune disorders, despite side effects, which include metabolic derangements such as central adiposity. These studies examine the role of protein phosphatase 5 (Ppp5) in glucocorticoid receptor (GR) complexes which mediate response to glucocorticoids. Mice homozygous for inactivated Ppp5 (Ppp5 D274A/D274A ) exhibit decreased adipose tissue surrounding the gonads and kidneys compared with wild-type mice. Adipocyte size is smaller, more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
(79 reference statements)
0
7
0
Order By: Relevance
“…In a recent study, we investigated the influence of the nematode PPH-5 protein, the TPR-containing phosphatase homolog to human Pp5, on the phosphorylation state of glucocorticoid receptor fragments and observed its dependency on the C. elegans Hsp90 (HSP-90) 41 . We see that the dephosphorylation of GR-fragments is enhanced in the presence of HSP-90 and this activity is conserved in the vertebrate system 41,42 . Nevertheless, the role of Pp5 during the assembly of GR•Hsp90 complexes is far from clear.…”
mentioning
confidence: 73%
“…In a recent study, we investigated the influence of the nematode PPH-5 protein, the TPR-containing phosphatase homolog to human Pp5, on the phosphorylation state of glucocorticoid receptor fragments and observed its dependency on the C. elegans Hsp90 (HSP-90) 41 . We see that the dephosphorylation of GR-fragments is enhanced in the presence of HSP-90 and this activity is conserved in the vertebrate system 41,42 . Nevertheless, the role of Pp5 during the assembly of GR•Hsp90 complexes is far from clear.…”
mentioning
confidence: 73%
“…A recent animal model study suggests a role of protein phosphatase 5 (PP5), which is supposed to be a regulator of the transcriptional activity of GR, in adipose tissue distribution. Mice knocked in with a defective form of PP5 had less VAT surrounding gonads and kidneys and smaller adipocytes, probably via a disruption of the GC-related effects on pre-adipocyte differentiation (92). GCs, via FOXO1, increase the expression of MKP3.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…MSCs were isolated from PP5 KO and WT mice following the protocol described in ref. 25 with a slight modification. MSCs were plated in a 60 mm cell culture dish at a density of 3 × 10 5 cells/ml.…”
Section: Methodsmentioning
confidence: 99%
“…PP5 contains a 34-amino acid tetratricopeptide repeat motif that mediates protein–protein interaction and also serves as an auto-inhibitory domain for phosphatase activity 22 , 23 . Genetic studies indicated that inactivation of PP5 prevented high-fat diet feeding-induced weight gain and adipogenesis 24 , 25 . Several studies have demonstrated that PP5 regulates both PPARγ and Runx2 through posttranscriptional and posttranslational mechanisms 26 28 .…”
Section: Introductionmentioning
confidence: 99%